Influence of glucose as a natural reductant on silver nanoparticles synthesis for decontamination of p-nitrophenol and methylene blue from wastewater - Ayman H. Mansee; Doaa M. Abdelgawad; Amal M. Ebrahim (Scientific Reports)
Abstract Silver nanoparticles (Ag°/glucose) were synthesized based on glucose as a natural reducing agent, aiming to develop an eco-friendly catalytic system. The characteristics of the produced Ag°/glucose were confirmed using standard nanomaterial characterization techniques. The optimum conditions for eliminating p-nitrophenol (PNP) and methylene blue (MB) from artificial polluted water using Ag°/glucose were systematically explored. Various kinetic and isotherm models were applied to elucidate the sorption mechanism and behavior. The synthesized Ag°/glucose exhibited a surface plasmon resonance (SPR) peak at 430 nm, with an average particle size ranging from 21 to 31 nm, and a zeta potential recorded as − 16 mV. The final concentration of Ag°/glucose was determined to be 1.2 × 10− 6 mol/L. During the first 15 min of incubation, a dose of 20 µL/mL Ag°/glucose achieved 53% and 74% removal of the targeted PNP and MB, respectively. Increasing the dose to 30 µL/mL showed a complete removal of both pollutants. Kinetic analysis revealed that the pseudo-second-order model was the best fitting model for both PNP and MB adsorption processes. Isothermal data showed a superior appropriateness of the present results to the Langmuir and Freundlich model for describing sorption behavior, with maximum adsorption capacities (q max ) of 2.5 E + 3and 1.0 E + 3 mg/g for PNP and MB, respectively.